Pengaruh Filler Nano Partikel White Karbon Aktif Kulit Bambu Terhadap Struktur (Photo Makro Dan SEM) Dan Kekuatan Tarik Komposit Polyester - Hidayat, Ervan; , Ir. Ngafwan, MT (2016)
ABSTRACT This study aimed to describe the effect of nano-particles of carbon white bamboo skin as a filler to the structure (photo macro & SEM) and tensile strength polyester composites. Methods of making composites by way of a press mold. Manufacture of composites using a variation filler weight fraction of carbon micro-particles of 0.1 grams, 0.15 grams and 0.2 grams of the polyester resin with the type Yukalac BQTN 157-EX. Micro mixing carbon particles with resin using methods stirring with the rotation speed of 2200 rpm for 10 minutes. Making test specimen using a standard tensile pull test ASTM D 638-01. Prior to the tensile test, conducted macro photo to know the composition of the carbon particles in the composite. From the results of photo macro distance and diameter values obtained micro carbon particles. The average distance in the specimen composite carbon particles with nano filler (FK) 0.1 grams of 48.8 μm, 0.15 at 39.59 FK and FK 0.2 μm amounting to 25.68 lm. The higher the weight fraction of carbon, the lower range of carbon particles. Diameter of carbon particles measured namely measuring 5.659 μm up to 21.982 lm. The results of tensile test tensile strength values obtained (yield) on average in the specimen Raw Material of 25.12 N / mm2, FK 0.1 grams of 28.4 N / mm2, FK 0.15 grams of 31.81 N / mm2 and FK 0.2 grams of 32.24 N / mm2. While the outline of the drop value (yield) on average in the specimen Raw Material by 0.73%, FK1% by 0.87%, 0.93% FK3% FK6% and 0.94%. In doing SEM on composite fault area, the results of SEM values obtained distance and diameter of carbon nano particles. The average distance to the composite specimens with nano filler particles of carbon white (FK) 0.1 grams of 0.577 μm, 0.477 μm of 0.15 FK and FK 0.2 of 0.464 lm. The higher the weight fraction of carbon, the lower range of carbon particles. Diameter of the nano-particles of carbon white measurable namely measuring 0.103 μm to 0.210 μm From the discussion of the test results it can be concluded that the addition of nano filler particles of carbon white were able to increase the tensile strength and tensile strain composite polyester.